Qualitative and Quantitative Analyses Of SMN 2 Gene Expression Upon Exposure with Histone De-acetylase Inhibitors and Polyphenols - Sasongko, Teguh Haryo (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Autosomal recessive SMA (Spinal Muscular Atrophy) is the second most common inherited disease, leading to early infancy death. The SMN1 mutations are leading cause of SMA. However, increasing expression of SMN2 has been exploited as therapeutic target for SMA. Several Histone Deacetylase Inhibitors (HDACIs) are known to increase SMN2 expression level. This study aimed to elucidate the effects of two hydroxamate-based HDACIs, SAHA and Dacinostat, and SRT1720, a synthetic SIRT1 activator with polyphenolic structure, on the SMN2 expression , CpG Islands (CGI) methylation and SMN protein levels in fibroblasts taken from SMA Type 1 and Type 11 patients. It was found that the levels of overall SMN2 gene expression (Overall-SMN2), SMN2 exon 7 inclusion (E7-SMN2) and SMN protein levels were significantly increased in 10 1-1M SAHA-treated Type 1 and Tvpe II cells. The mean methylation level was significantly lower. Accordingly, the level of Overall-SMN2 and E7-SMN2 transcript increase were also significant. The transcript increase induced by Dacinostat led to more increase of SMN protein compared to SAHA in Type 1 cells (2.54 ± 1.57 fold). SMN2 gene expression (Overall-SMN2 and E7-SMN2) was also increased upon exposure to SRT1720. The mean CGIs methylation percentage and SMN protein level alteration were decreased modestly SAHA-Dacinostat combination increased SMN2 express1on in Type I, but not Type II cells. SRT1 720-Dacinostat combination increase Overall-SMN2 and E7-SMN2 transcripts nearly double the increase induced by individual compounds. SRT1720-SAHA combination resulted in lower increase than that induced by SAHA alone but higher increase than that induced by SRT1720 alone. Furthermore, SMN protein was noted to be increased and CGIs was more demethylated in treated cells. In conclusion, SMN2 expression (Overall-SMN2 and E7 -SMN2), SMN protein level and methylation level of CGIs were significantly altered upon exposure to SAHA, Dacinostat and SRT1720-Dacinostat combination in SMA fibroblast Type I and Type II . This is the first report about Dacinostat and SRT1720 effect on SMN2 modulation.